Detoxification of aflatoxins in fermented cereal gruel (Ogi) by probiotic lactic acid bacteria and yeasts with differences in Amino Acid profiles - Banwo, K.; Adesina, T.; Aribisala, O.R.; Falade, T.D.O. (MDPI, 2023)
Toxigenic members of Aspergillus flavus contaminate cereal grains, resulting in contamination by aflatoxin, a food safety hazard that causes hepatocellular carcinoma. This study identified probiotic strains as aflatoxin detoxifiers and investigated the changes to the grain amino acid concentrations during fermentation with probiotics in the presence of either A. flavus La 3228 (an aflatoxigenic strain) or A. flavus La 3279 (an atoxigenic strain). Generally, higher concentrations (p < 0.05) of amino acids were detected in the presence of toxigenic A. flavus La 3228 compared to the atoxigenic A. flavus La 3279. Compared to the control, 13/17 amino acids had elevated (p < 0.05) concentrations in the presence of the toxigenic A. flavus compared to the control, whereas in systems with the atoxigenic A. flavus 13/17 amino acids had similar (p > 0.05) concentrations to the control. There were interspecies and intraspecies differences in specific amino acid elevations or reductions among selected LAB and yeasts, respectively. Aflatoxins B1 and B2 were detoxified by Limosilactobacillus fermentum W310 (86% and 75%, respectively), Lactiplantibacillus plantarum M26 (62% and 63%, respectively), Candida tropicalis MY115 (60% and 77%, respectively), and Candida tropicalis YY25, (60% and 31%, respectively). Probiotics were useful detoxifiers; however, the extent of decontamination was species- and strain-dependent. Higher deviations in amino acid concentrations in the presence of toxigenic La 3228 compared to atoxigenic La 3279 suggests that the detoxifiers did not act by decreasing the metabolic activity of the toxigenic strain.